Image Enhancement and Effective Recruitment Strategies in the Brokerage Industry Pt. Victory International Futures : Strategi Peningkatan Citra dan Efektivitas Rekrutmen Pada Industri Pialang PT. Victory Internasional Futures - Nurul Haromaini; Hery Pudjoprastyono (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The commodity futures brokerage industry in Indonesia faces serious challenges in building a positive image due to low public financial literacy and rampant cases of illegal investment fraud. This condition has a direct impact on the effectiveness of labor recruitment, as negative perceptions discourage potential applicants from joining the sector. This community service aims to increase public understanding of the legality of futures investment and strengthen the image of the brokerage company PT Victory Internasional Futures to support a more effective recruitment process. The method used is descriptive qualitative through observation and interviews, as well as the implementation of an educational webinar entitled “Peel Through Futures Trading”. The results showed an increase in participants' understanding of futures trading mechanisms, company legality, and available career opportunities. Digital communication strategies through social media, testimonials, and collaboration with educational institutions have also proven effective in attracting qualified applicants and shifting negative public perceptions. Systematic public education and a structured recruitment approach are key to addressing industry stigma and challenges. The results of this activity emphasize the importance of collaboration between financial literacy and employer branding strategies in creating a sustainable and trusted recruitment system.